The Influence of Financial Capital and Financial Management on the Performance of MSMEs at the Mentaya Shooping Center in Sampit - Glorianismus, Filoshopia Yasni; Sambung, Roby; Ani Mahrita; Pratiwi Hamzah (PT Mattawang Mediatama Solution, 2025)
This study aims to analyze the influence of financial capital and financial management on the performance of Micro, Small, and Medium Enterprises (MSMEs) at the Mentaya Shopping Center in Sampit, Central Kalimantan. Using a quantitative approach with a survey method, data were collected from 82 MSME respondents and analyzed through Structural Equation Modeling using SmartPLS 4.0. The research reveals that both financial capital and financial management have a positive and significant effect on MSME performance, both individually and simultaneously. The coefficient of determination (R²) value of 0.612 indicates that 61.2% of the variation in MSME performance is explained by the two independent variables. The findings show that most MSMEs rely on internal capital and face challenges accessing external financing. At the same time, financial management practices—especially in recording, reporting, and controlling—are still not fully optimized. The research supports the Resource-Based View (RBV) and Financial Capability Theory, which emphasize that a combination of financial resources and managerial competence is critical to enhancing business performance. Strategic implications highlight the importance of integrated interventions from stakeholders to improve access to capital and financial literacy among MSME actors. Programs combining digital finance access with structured financial training can significantly enhance MSME competitiveness, especially in traditional market settings. The study contributes both theoretically and practically to the development of inclusive economic models for MSME sustainability in regional markets.